Nodal metastasis in cervical cancer occurs in clearly delineated fields of immune suppression in the pelvic lymph catchment area - Heeren, A. Marijne (Oncotarget, 2015)
In cervical cancer, high frequencies of regulatory T cells (Tregs) and immunosuppressive PD-L1(+)CD14(+) antigen-presenting cells dominate the microenvironment of tumor-positive lymph nodes (LN+). It is unknown whether this is restricted to LN+ or precedes metastasis, emanating from the primary tumor and spreading through tumor-draining lymph nodes (TDLNs). To investigate immunosuppression in the lymphatic basin of cervical tumors, all dissected TDLNs of five cervical cancer patients (in total 9 LN+ and 74 tumor-negative lymph nodes (LN−)) were analyzed for FoxP3(+) Tregs, CD8(+) T cells, HLA-DR(+)- and PD-L1(+) myeloid cells by immunohistochemistry. Tregs and PD-L1(+) cells were found to form an immunosuppressive cordon around metastatic tumor cells. Importantly, whereas high HLA-DR(+)- and PD-L1(+) cell rates were strongly associated with LN+, elevated Treg levels and decreased CD8(+) T cell/Treg ratios were found similar in LN+ and adjacent LN−, as compared to LN− at more distant anatomical localizations. These data suggest that delineated fields of Treg-associated immune suppression in anatomically co-localized TDLNs enable metastasis by creating metastatic niches. This may be of importance for decision-making regarding (surgical) intervention in cervical cancer. Future efforts should include the implementation of immunotherapeutic regimens to overcome this immune suppression, establish loco-regional control and halt systemic tumor spread.